2019
DOI: 10.1155/2019/5980465
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Delays Satellite Cell Activation and Maintains Quiescence

Abstract: The regeneration of the muscle tissue relies on the capacity of the satellite stem cell (SC) population to exit quiescence, divide asymmetrically, proliferate, and differentiate. In age-related muscle atrophy (sarcopenia) and several dystrophies, regeneration cannot compensate for the loss of muscle tissue. These disorders are associated with the depletion of the satellite cell pool or with the loss of satellite cell functionality. Recently, the establishment and maintenance of quiescence in satellite cells ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 52 publications
4
30
2
Order By: Relevance
“…Therefore, it is plausible that metformin treatment provides more energy to proliferating satellite cells thus enhancing their ability to regenerate and repair damaged myofibers after burn injury. Recently, Pavlidou et al reported that metformin reduced the number of Pax7 + /BrdU + muscle progenitor cells and depleted skeletal muscle regeneration, a finding contrary to ours [75]. The differences between the two studies may be the nature of the injury.…”
Section: Discussioncontrasting
confidence: 84%
“…Therefore, it is plausible that metformin treatment provides more energy to proliferating satellite cells thus enhancing their ability to regenerate and repair damaged myofibers after burn injury. Recently, Pavlidou et al reported that metformin reduced the number of Pax7 + /BrdU + muscle progenitor cells and depleted skeletal muscle regeneration, a finding contrary to ours [75]. The differences between the two studies may be the nature of the injury.…”
Section: Discussioncontrasting
confidence: 84%
“…Freshly isolated satellite cells were plated at a density of 15,000 cells/cm 2 on matrigel-coated 96-well plates at 37 °C and 5% CO 2 in satellite cell Growth Medium (sGM) composed of DMEM, 20% FBS, 10% Horse Serum (Euroclone, #ECS0090D), 2% Chicken Embryo Extract (Seralab, # CE-650-J) 65 . Prior to starting any experiment, freshly isolated SCs were cultured for at least 48 hours before treatment to allow cell adhesion.…”
Section: Satellite Cell and Fap Isolationmentioning
confidence: 99%
“…Chronic inflammation is a typical hallmark of DMD and may contribute to impaired skeletal muscle regeneration. Although many cells are involved in chronic inflammation, one of the most important roles is played by macrophages, since these cells are associated not only to satellite cells’ activation but also to the survival of fibro/adipogenic progenitors (FAPs), which outcompete the satellite cell population during inflammation [ 44 ]. By competing with satellite cells, FAPs can increment the fibrotic process; an imbalance between the two populations ultimately leads to the accumulation of FAPs in skeletal muscles with consequent aberrant production of pro-fibrotic factors (e.g., ECM components).…”
Section: Duchenne Muscular Dystrophy: Is There a Role For Satellitmentioning
confidence: 99%
“…Then, it is feasible that the molecular mechanism underlying the anti-fibrotic action (still under clarification for MET) or other parallel mechanisms can define the outcome on regeneration efficiency [ 121 ]. Interestingly, Pavlidou et al recently reported that, in C57BL/6 mice, MET delayed satellite cell activation and maintained quiescence (as shown by reduced Pax7 protein expression) [ 44 ].…”
Section: Pharmacological Approaches Targeting Niche Homeostasis: Wmentioning
confidence: 99%